Cardiac resynchronization therapy and electrical storm: results of the OBSERVational registry on long-term outcome of ICD patients (OBSERVO-ICD). Issue 6 (7th June 2017) - Guerra, Federico; Palmisano, Pietro; Dell'Era, Gabriele; Ziacchi, Matteo; Ammendola, Ernesto; Pongetti, Giulia; Bonelli, Paolo; Patani, Francesca; Devecchi, Chiara; Accogli, Michele; Occhetta, Eraldo; Nigro, Gerardo; et al.
Abstract: Aims: Electrical storm (ES) is a condition defined as three or more episodes of ventricular fibrillation (VF) or ventricular tachycardia (VT) within 24 h, and usually coexist with advanced heart failure in patients with structural heart disease. The aim of the present study is to test whether cardiac resynchronization therapy (CRT) can be associated with a lower incidence of ES. Methods and results: The OBSERVO-ICD (NCT02735811) is a multicentre, retrospective registry, enrolling all consecutive patients undergoing ICD or CRT-D implantation from 2010 to 2012 in five Italian high-volume arrhythmia centres. Propensity score matching was used to compare two equally sized cohorts of ICD and CRT-D patients with similar characteristics. The primary endpoint was the time free from ES. Secondary endpoints were time free from unclustered VT/VF episodes and time free from ES in CRT-D patients according to clinical or echographic response. CRT-D was associated with a 45% relative risk reduction in ES when compared with ICD (5.6% vs. 12.3%; log rank P  = 0.014). CRT-responders presented lower rates of ES when compared with non-responders and negative responders according to both clinical and echographic criteria (log-rank P  = 0.017 and 0.023, respectively). No ES was detected in any of the 133 full responders to CRT-D. Clinical and echographic positive responses, but not CRT-implant per se, were associated with lower estimate rates of unclustered VTs/VFs. Conclusion: Patients with CRT had a lower incidence of ES when compared with propensity-matched ICD patients. The long-term benefit of CRT seems to be due to the improved haemodynamics, as CRT-responders performed markedly better over a long-term follow-up.